Legal Protection For Child Victims of Partner Violence: A Perspective From Law Number 35 of 2014 Concerning Child Protection - Vratista, Imelda; Lewoleba, Kayus Kayowuan (Dinasti Research, 2025)
This research discusses legal protection for child victims of dating violence in Indonesia, referring to Law Number 35 of 2014 concerning Child Protection. The phenomenon of dating violence among children and adolescents is becoming increasingly normalized by society, yet the available legal protection is still inadequate. The purpose of this research is to analyze the challenges and formulate efforts in implementing effective legal protection for children who are victims of dating violence. This research uses a normative juridical method with a legislative, conceptual, and legal implications approach. The research findings indicate three main challenges: the absence of legal norms due to the lack of explicit regulations regarding dating violence in the Child Protection Law, obstacles to reporting and accessing justice due to low awareness and social stigma, and weak inter-agency coordination in implementing child protection. The Indonesian Child Protection Commission (KPAI) has attempted to overcome these obstacles thru strengthening institutional synergy, policy advocacy, digital-based monitoring, and promoting responsive local regulations. However, the implementation of legal protection has not been comprehensive due to the limited understanding and sensitivity of law enforcement officials and the public. Therefore, legal updates are needed by including dating violence as a form of violence against children, increasing public legal literacy, and strengthening cross-sectoral coordination to realize child protection in accordance with the principle of the best interests of the child.